Alternate Admissibility LMI Criteria for Descriptor Fractional Order Systems with 0 < α < 2 - Ying Di; Jin-Xi Zhang; Xuefeng Zhang (Fractal and Fractional, 2023)
The paper focuses on the admissibility problem of descriptor fractional-order systems (DFOSs). The alternate admissibility criteria are addressed for DFOSs with order in <semantics>(0,2)</semantics> which involve a non-strict linear matrix inequality (LMI) method and a strict LMI method, respectively. The forms of non-strict and strict LMIs are brand new and distinguished with the existing literature, which fills the gaps of studies for admissibility. These necessary and sufficient conditions of admissibility are available to the order in <semantics>(0,2)</semantics> without separating the order ranges into <semantics>(0,1)</semantics> and <semantics>[1,2)</semantics>. Based on the special position of singular matrix, the non-strict LMI criterion has an advantage in handling the DFOSs with uncertain derivative matrices. For the strict LMI form, a method involving least real decision variables is derived which is more convenient to process the practical solution. Three numerical examples are given to illustrate the validity of the proposed results.